1994
DOI: 10.1007/bf03344960
|View full text |Cite
|
Sign up to set email alerts
|

Normal plasma insulin-like growth factor I levels and impaired final stature in adult blind subjects

Abstract: The aim of this study was to determine if changes in IGF-1 levels and in final stature occur in blind adult subjects. Eighteen subjects (4 females and 14 males) with total blindness (Group 1) and 26 subjects (5 females and 21 males) with only light perception (Group 2), living at an Institute for blind adult subjects in Naples, Italy, were studied. Their height and weight were compared to British standards. Plasma morning IGF-1 levels, measured by IRMA method were compared to those of 18 normal controls (6 fem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

1997
1997
2010
2010

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 21 publications
0
6
0
Order By: Relevance
“…It has been argued, for example, that increased exposure to sunshine during the first trimester of gestation may inhibit maternal melatonin production and stimulate the release of growth hormone (GH). Although high levels of melatonin are typically associated with high levels of GH (Laartz, Losee-Olson, Ge, & Turek, 1994;Zeman, Buyse, Lamosová, Herichová, & Decuypere, 1999), there is some evidence in both deer (Webster, Corson, Littlejohn, Stuart, & Suttie, 1998) and humans (Bellastella et al, 1994) for an inverse relation between melatonin and GH production. From this perspective, greater exposure to light during the first trimester of gestation may increase GH levels by inhibiting melatonin production.…”
Section: Discussionmentioning
confidence: 97%
“…It has been argued, for example, that increased exposure to sunshine during the first trimester of gestation may inhibit maternal melatonin production and stimulate the release of growth hormone (GH). Although high levels of melatonin are typically associated with high levels of GH (Laartz, Losee-Olson, Ge, & Turek, 1994;Zeman, Buyse, Lamosová, Herichová, & Decuypere, 1999), there is some evidence in both deer (Webster, Corson, Littlejohn, Stuart, & Suttie, 1998) and humans (Bellastella et al, 1994) for an inverse relation between melatonin and GH production. From this perspective, greater exposure to light during the first trimester of gestation may increase GH levels by inhibiting melatonin production.…”
Section: Discussionmentioning
confidence: 97%
“…16 These findings are consistent with reports by Bellastella and Leger, who reported that blind people with varying degrees of light perception are shorter in stature and have a lower BMI than sighted controls. 2,3,17 The increased current BMI in NPL women does not account for the earlier menarche observed in this group, as could be hypothesized, 18 as their weight and BMI were significantly lower than LP women at age 18. Consistent with prior reports, we found no differences between LP and NPL women in age at natural menopause, which occurred around age 50.…”
Section: Discussionmentioning
confidence: 57%
“…The blind population has been shown to differ from the sighted population in that blind women are reportedly shorter in stature and have a lower BMI. 2,3 Further, menarche in blind women has been reported to be both earlier and the same as in sighted women. 4−6 Women with no perception of light (NPL) compared to women with light perception (LP) have been reported to have no differences in menopause or fertility.…”
Section: Introductionmentioning
confidence: 92%
“…Blindness has been shown to impair the growth of prepubertal [39] and the final stature of adult [40] institutionalized subjects. In this connection a negative influence of blindness on GH secretion has been described both in animals and in man.…”
Section: Growth and Growth Hormone (Gh) Secretionmentioning
confidence: 99%
“…A possible inhibiting action of MT on GH secretion, as demonstrated in animals [41], can be supposed also in man taking into account the high levels of MT in blind subjects [22, 23, 24, 25], even if exogenous administration of MT in man has been shown either to suppress [45, 46] or increase [47] GH secretion. However, since blind people show normal insulin-like growth factor I (IGF-I) levels, blindness could influence negatively the growth through complex mechanisms which do not involve only GH and IGF-I axis [40]. …”
Section: Growth and Growth Hormone (Gh) Secretionmentioning
confidence: 99%